THE INFLUENCE OF LDR AND NPL ON THE PROFITABILITY OF RURAL BANKS: A SYSTEMATIC LITERATURE REVIEW (2021–2025) - Anwar, Khairil; Pardosi, Pardomuan; Sulistyowati, Tussi; Maia, Fonseca de Jesus; Setiawan, Ervan (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
Profitability is a key indicator of the sustainability of Rural Banks (BPR), which play an important role in supporting local economies. This study systematically reviews the relationship between Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), and BPR profitability using a Systematic Literature Review (SLR) approach. Articles were selected from reputable international databases published between 2015 and 2024 based on topic relevance and empirical methodology. The findings reveal that LDR has a positive impact on profitability when managed proportionally, while NPL has a significant negative effect due to increased credit risk. Rural BPR face greater challenges compared to commercial banks because of limited asset diversification and dependence on micro-agricultural sectors. This study highlights the importance of risk management, adaptive regulation, and digitalization of banking services as strategies to enhance BPR performance, and provides theoretical and practical insights for policy and managerial development.